Influence of the Alloying Elements on the Corrosion Behavior of As-Cast Magnesium–Gallium–Zinc Alloys in Simulated Body Fluid - Anabel A. Hernández-Cortés; José C. Escobedo-Bocardo; Dora A. Cortés-Hernández (Metals, 2023)
The in vitro corrosion rate of as-cast ternary Mg-Ga-Zn alloys in simulated body fluid (SBF) was evaluated. The effects of Ga3+ and Zn2+ on the formation, growth and stability of Ca, P-rich compounds on the surface of the ternary alloys, and the effect of these compounds on corrosion rate, were studied. Ternary Mg-Ga-Zn alloys (Ga from 0.375 to 1.5 wt% and Zn from 1.5 to 6 wt%) were obtained and then immersed in SBF to evaluate the corrosion rate using the weight loss method. The species formed on the alloys surface were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FT-IR). The formation of amorphous Ca, P-rich compounds on the alloys was observed. The species formed are related to the corrosion rate and the ions released into the SBF. The Mg, Ga and Zn ions released into the SBF during the corrosion process of the studied alloys play an important role in the growth of the Posner’s clusters, propitiating the reduction in size of the Ca, P-rich agglomerates. The corrosion rate of these as-cast ternary alloys increased as the intermetallics formed increased. The amount and size of the intermetallics formed depend on the Ga and Zn concentration in the alloys.